USE OF MODERN TECHNOLOGIES IN TEACHING ENGLISH (American Journal of Technology and Applied Sciences, 2023)
The digital era is a creator of learning modern English language from the youngest population to the three cycles of the higher education system. Internet connections and technological innovations transformed into modern tools such as computers, tablets, smartphones, smartwatches upgraded with modern platforms such as Moodle, Blackboard, etc., are not only a necessity but also an obligation of every individual and institution for advanced and modern learning of English Language.